Institutional transformation to engage a diverse student body - Thomas, Liz (Elizabeth); Tight, Malcolm (International perspectives on higher education research, 2011)
It is now widely accepted that institutional change is necessary to engage a diverse student body, both to encourage them to enter higher education (HE), and to enable them to be successful in HE. This book is premised on the need for institutional transformation: changing institutional structures, processes and governance; developing an inclusive culture and altering processes of knowledge creation (research) and knowledge transfer (learning and teaching). Key features of the book include: Developing the concept of institutional transformation and student engagement to widen participation in HE and improve student retention and success; Providing an analysis of how well institutions in England are doing in terms of taking a whole institution approach to widening participation, student diversity and success. Exploring the meaning of institutional transformation in relation to: outreach, admissions, induction and transition, learning and teaching, personal tutoring and support, research and progression beyond HE. Identifying approaches to managing institutional transformation. Involving students in the process of transformation. Illustrating and developing these themes through a serious of mini international case studies. The book aims to help readers engage with a number of the core higher education issues that have dominated UK and International policy over recent years.